2018
DOI: 10.1371/journal.pgen.1007440
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides modulate long-term memory

Abstract: Antimicrobial peptides act as a host defense mechanism and regulate the commensal microbiome. To obtain a comprehensive view of genes contributing to long-term memory we performed mRNA sequencing from single Drosophila heads following behavioral training that produces long-lasting memory. Surprisingly, we found that Diptericin B, an immune peptide with antimicrobial activity, is upregulated following behavioral training. Deletion and knock down experiments revealed that Diptericin B and another immune peptide,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 46 publications
(70 reference statements)
2
60
0
Order By: Relevance
“…Several of these transcripts have been identified in previous studies (Table S3), albeit under different conditions (e.g. courtship, social defeat) ( Barajas-Azpeleta et al, 2018;Carney, 2007;Ellis and Carney, 2011;Mohorianu et al, 2017;Wang et al, 2008) or by different techniques (e.g. microarray, RNA-seq).…”
Section: Social Isolation Induces Transcriptional Changes In Male Dromentioning
confidence: 70%
See 1 more Smart Citation
“…Several of these transcripts have been identified in previous studies (Table S3), albeit under different conditions (e.g. courtship, social defeat) ( Barajas-Azpeleta et al, 2018;Carney, 2007;Ellis and Carney, 2011;Mohorianu et al, 2017;Wang et al, 2008) or by different techniques (e.g. microarray, RNA-seq).…”
Section: Social Isolation Induces Transcriptional Changes In Male Dromentioning
confidence: 70%
“…Finally, we would note that new roles have recently been proposed for transcripts annotated as encoding antimicrobial peptides (e.g. Diptericin B, DptB), specifically the modulation of long-term memory (Barajas-Azpeleta et al, 2018). It is possible that some of the transcripts annotated as antimicrobial peptides are instead (or in addition) memory regulators with roles in social behaviors.…”
Section: Social Experience Modulates Gene Expression In Drosophila Headsmentioning
confidence: 96%
“…For instance, an AMP may kill microbes and also attract macrophages to the site of infection (Diamond et al 2009). Recently, AMPs were reported to play an important role in memory formation, with functions in both brain and fat body (Barajas-Azpeleta et al 2018). With NUR, we suggest that the second function is to promote survival by increasing sleep.…”
Section: Crispr-cas9 Techniquementioning
confidence: 92%
“…Induction of enhanced immune response and development of memory against a specific stimuli are based on the past experience and are important for survival (Barajas‐Azpeleta et al 2018). The recent insight in trained immunity has demonstrated that it could have future implications for the development of novel strategies for microbe‐mediated diseases.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%